Understanding sin in Zairian society from the perspective of Reinhold Nielbuhr's theology - Kasongo, Muteho ([n.p.] South East Asia Graduate School of Theology, 1999)
This thesis sought to explore the nature of sin in society in order to bring people. Particularly the state and the church. To find an appropriate remedy
The main problem is : how can people deal realistically with sin in society in order to bring more human dignity in society
In partial fulfillment of the requirements for the degree Master of Theology (Systematic Theology).
Thesis presented to the faculty of South East Asia Graduate School of Theology
Thesis (M. Theo.) - South East Asia Graduate School of Theology